STUDY OF URBAN HEAT ISLAND AND ITS CORRELATION WITH LAND USE CHANGE IN JAKARTA - Rizki, Muhammad
The rapid development of Jakarta, especially in the development of both residential and industrial areas are very interesting to examine as the distribution of the surface temperature. Studies on Urban Heat Island (UHI) mapped the dispersion of surface temperatures processed from channels of 10 Landsat 8 satellite imagery. Data processing of LANDSAT satellite imagery 8 Canal 10 is done through several stages and correction of values, starting from converting digital numbers to spectral radians, converting spectral radians to brightness temperatures, calculating NDVI (Normalized Difference Vegetation Index), and correcting emissivity to get a good surface temperature value. Meanwhile, for classifying land cover used the supervised classification method and grouped into six classes, vegetation, population settlements, industries, open land, water bodies, and clouds. The area of the surface temperature and the land cover will be analyzed to see how they are associated. The results showed that there was a rise in the surface temperature from 2013 as the initial year of the study and year 2018 as the final year of the study, the surface temperature value above 35 °C including an increase in a surface change in land area by 5339.7 ha. Land built such as settlements and industries have the greatest effect on changes in surface temperature that trigger Urban Heat Island.